Evidence and patterns of maternal transfer of metals and trace elements in Western tiger snakes (Notechis scutatus occidentalis) – a pilot study - Lettoof, Damian C.; Van Dyke, J.U.; Gagnon, Marthe Monique (WILEY, 2021)
Urban wildlife are regularly exposed to a variety of anthropogenic contaminants that have the potential to bioaccumulate in body tissues. As a consequence, developing embryos and offspring can be at risk from exposure to maternally accumulated contaminants, yet this has rarely been reported in reptiles. We opportunistically collected one pregnant Western tiger snake (Notechis scutatus occidentalis) from each of three wetlands with differing sediment metal contamination around Perth, and analysed maternal snake livers and three foetuses per litter for a suite of 17 elements representing either alkaline earth metals, transition metals or metalloids. We detected 14 elements, and compared their concentrations in maternal livers to foetus whole bodies to determine preliminary patterns of maternal transfer. Our results suggest antimony, arsenic, manganese, mercury, molybdenum and zinc are maternally transferred in Western tiger snakes. We urge further research to further quantify patterns of contaminant maternal transfer in viviparous snakes and determine their impacts on the development and health of contaminated offspring.